Growth, Grazing, and Starvation Survival in Three Heterotrophic Dinoflagellate Species. (19th September 2016) - Anderson, Sean R.; Menden‐Deuer, Susanne
Abstract: To assess the effects of fluctuating prey availability on predator population dynamics and grazing impact on phytoplankton, we measured growth and grazing rates of three heterotrophic dinoflagellate species— Oxyrrhis marina, Gyrodinium dominans and Gyrodinium spirale— before and after depriving them of phytoplankton prey. All three dinoflagellate species survived long periods (> 10 d) without algal prey, coincident with decreases in predator abundance and cell size. After 1–3 wks, starvation led to a 17–57% decrease in predator cell volume and some cells became deformed and transparent. When re‐exposed to phytoplankton prey, heterotrophs ingested prey within minutes and increased cell volumes by 4–17%. At an equivalent prey concentration, continuously fed predators had 2‐fold higher specific growth rates (0.18 to 0.55 d −1 ) than after starvation (−0.16 to 0.25 d −1 ). Maximum specific predator growth rates would be achievable only after a time lag of at least 3 d. A delay in predator growth poststarvation delays predator‐induced phytoplankton mortality when prey re‐emerges at the onset of a bloom event or in patchy prey distributions. These altered predator‐prey population dynamics have implications for the formation of phytoplankton blooms, trophic transfer rates, and potential export of carbon.